CULTURAL LINGUISTIC STUDIES OF THE CONCEPTS: FRAME ANALYSIS - Mukhammadiyarov Aydos Joldasbaevich; Tajiyeva Aliya Utebaevna (KONFERENSIYALAR, 2025)
Annotation. The given article reveals that cultural linguistic peculiarities are expressed based on the concept especially in the field of translation studies. The main method to analyze translated Byron’s poem in Karakalpak is to find out basic lexical frames which can help us to conceptualize human soul universally. Doing the frame (framing) analysis by which Ervin Goffman started to use in his book, we identified that the «soul» is the main concept in people connecting with love, sorrow, motherland, longing, and despair and in translations of the poems «Lines written in an album» by Byron the «soul» was shown similarly both in meaning and translating. In the end, the essential frames like traveler, a dead person, grave, remedy, bridge, darkness, can help one to embody the author’s soul and were classified into framing subgroups, such as linguistic frame, emotional and spiritual frame, metaphorical frame, philosophical frame, structural frame, contextual frames.